2017
DOI: 10.1007/s00432-017-2522-3
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death and competing risk analysis of the associated factors for non-small cell lung cancer using the Surveillance, Epidemiology, and End Results database

Abstract: Most of the patients with NSCLC died from lung cancer. Rational surveillance and treatment policies should be made for them. Early stage and lobectomy or bilobectomy were associated with improved OS and LCSS. It is reasonable to focus on early detection and optimal surgical treatment for NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 32 publications
5
25
0
Order By: Relevance
“…Previous studies with early-stage NSCLC have shown that age had an adverse effect on both lung cancer and non-lung cancer specific survival. 12,27,34 These findings were in agreement with our results.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Previous studies with early-stage NSCLC have shown that age had an adverse effect on both lung cancer and non-lung cancer specific survival. 12,27,34 These findings were in agreement with our results.…”
Section: Discussionsupporting
confidence: 94%
“…Considering that the median age at diagnosis of lung cancer patients is 70 years, it is not surprising that many of them have comorbidities and increased risk for non–lung cancer mortality after lung resection . Recent studies found that deaths from cardiovascular diseases (CVD) and chronic obstructive pulmonary diseases (COPD) become increasingly important in patients undergoing surgical resection during follow up, especially among older patients . It is unclear whether lobectomy and sublobectomy display different patterns of long‐term postoperative non‐lung cancer mortality and no correlational analysis in a large cohort have been published.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other clinical factors associated with poor prognosis are tumor grade (Sun et al, 2006), increasing age, male gender, smoking status, performance status, comorbidity, and surgical technique (Bugge et al, 2018;Wei et al, 2018;Woodard et al, 2016). Different prognostic biomarkers have been investigated but this far none have been enough validated to make its way to the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the most common cause of cancer‐related death in the world . Despite advances in therapy, the overall survival rate of patients with advanced lung cancer is low.…”
Section: Introductionmentioning
confidence: 99%